Inhibitory effect of procaterol on exercise dynamic lung hyperinflation during the 6-min walk test in stable patients with chronic obstructive pulmonary disease - Satake, Masahiro; Takahashi, Hitomi; Sugawara, Keiyu; Kawagoshi, Atsuoshi; Tamaki, Akira; Homma, Mitsunobu; Morita, Ryou; Sato, Kazuhiro; Sano, Masaaki; Shioya, Takanobu (Arzneimittelforschung, 2011)
The purpose of this study was to evaluate the inhibitory effect of procaterol (procaterol hydrochloride, CAS 62929-91-3) on exercise dynamic lung hyperinflation during the 6-min walk test (6MWT) in stable chronic obstructive disease (COPD) patients. Fourteen patients with stable COPD who were referred to our clinic between July 2008 and October 2009 were evaluated in this study. After the inhalation of procaterol, values for the lung function test, including vital capacity, inspiratory capacity, forced vital capacity, and FEV1/FEV1pred showed a significant improvement. Compared to the baseline assessment, the 6-min walk distance increased by a mean of 20.5 m when measured after inhalation of procaterol (512.4 ± 90.7mvs. 532.9 ± 79.8 m, p < 0.05). During the 6MWT, inspiratory capacity decreased significantly with time. The inspiratory capacity after inhalation of procaterol was improved significantly compared with placebo. The Borg scale increased significantly during the 6MWT and was attenuated after inhaling procaterol hydrochloride, though the difference between the two groups was not statistically significant.In the present study, there was a significant attenuation in exercise dynamic lung hyperinflation, suggesting the important role of the β2-receptor agonist procaterol in the treatment of COPD. It is therefore likely that most patients with COPD may derive considerable benefit from bronchodilator therapy with procaterol.
Keywords: β2-Receptor agonist; Bronchodilator; CAS 62929-91-3; Dyspnea; End-expiratory lung volume; Exercise dynamic lung hyperinflation; Procaterol hydrochloride; Six-minute walk test